Progressive Educational Leadership in Strengthening the Pedagogical Competence of Elementary School Teachers : Kepemimpinan Pendidikan Progresif Dalam Menguatkan Kompetensi Pedagogik Guru Sekolah Dasar - Sundari Sundari; Harun Joko Prayitno; Bambang Sumardjoko (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Teachers' pedagogical competence is crucial in realizing meaningful learning, but elementary school teachers face many challenges and require the progressive educational leadership of the principal to drive and strengthen it. This research aims to analyze progressive educational leadership in strengthening primary school teachers' pedagogical competence. The research used a qualitative approach with a case study design, conducted at one of the public elementary schools in Kebakkramat District, Karanganyar, with the principal and teachers as subjects. Data was collected through observation, interviews, and document studies. Data was analyzed through data reduction, data presentation, and conclusion drawing. Data was validated through source and technique triangulation. The research findings indicate that the progressive educational leadership implemented by the principal through the roles of leading learning, developing people, and building collaborative cultures is capable of comprehensively strengthening teachers' pedagogical competence. Teachers become more capable of designing learning according to students' characteristics, implementing effective and adaptive learning, and conducting continuous evaluation, reflection, and follow-up of learning. The progressive educational leadership of school principals plays a strategic role in strengthening the pedagogical competence of elementary school teachers, so it needs to be consistently implemented through reflective supervision, continuous mentoring, and strengthening a collaborative culture in schools.